Hepatoprotective effects of Flagellaria indica are mediated through the suppression of pro-inflammatory cytokines and oxidative stress markers in rats. (2nd August 2016) - Gnanaraj, Charles; Shah, Muhammad Dawood; Makki, Jaafar Sadeq; Iqbal, Mohammad
Abstract: Context The antioxidative properties of plants or plant derivative products are well known for their free radical scavenging effects. Flagellaria indica L. (Flagellariaceae) (FI) is a tropical medicinal plant used by the natives of Sabah as medication for semi-paralysis. Objective This study evaluates the hepatoprotective mechanism of FI against carbon tetrachloride (CCl4 )-mediated liver damage. Materials and methods Aqueous extract of FI leaves was orally administered to adult Sprague–Dawley rats once daily for 14 consecutive days at 300, 400, and 500 mg/kg b.w. prior to CCl4 treatment (1.0 mL/kg b.w.) on the 13th and 14th days. Results Total phenolic content in the aqueous extract of FI leaves was 65.88 ± 1.84 mg gallic acid equivalent/g. IC50 value for free radical scavenging activity of FI aqueous extract was reached at the concentration of 400 μg/mL. Biochemical studies show that the aqueous extract of FI was able to prevent the increase in levels of serum transaminases, alanine aminotransferase, and aspartate aminotransferase (38–74% recovery), and malondialdehyde formation (25–87% recovery) in a dose-dependent manner. Immunohistochemical results evidenced the suppression of oxidative stress markers (4-hydroxynonenal and 8-hydroxydeoxyguanosine) and pro-inflammatory markers (tumour necrosis factor-α, interleukin-6, prostaglandin E2 ). Histopathological and hepatocyte ultrastructural alterations proved that there were protective effects in FI against CCl4 -mediated liver injury. Signs of toxicity were not present in rats treated with FI alone (500 mg/kg b.w.). Discussion and conclusion It can be concluded that the presence of phenolic constituents and their antioxidative effects can be credited to the hepatoprotective activity of FI.